New York [videorecording (DVD)]. - Brown, Mason B. E. (Discoveries-- America., 2006)
Visit New York City, the Statue of Liberty, the Hudson Valley, Sarasota Springs, the Adirondack State Park, the Erie Canal, Niagara Falls, and much more.